Smart interior designs for sustainable workspaces: insights from shop-lot offices in tropical regions - Awang, Arita Hanim (Nova Science Publishers, 2025)
This chapter investigates the potential liability of smart interior design to enhance the sustainability in shop office workspaces within tropical climates—Shop-lot offices, in tropical regions. Shop-lot offices, which are a prevalent architectural typology in tropical regions, present unique design challenges, such as high temperatures, humidity, and reliance on air-conditioning systems. Through a thorough systematic literature review, this study examines was conducted to examine how smart interior design principles encompassing, such as adaptive lighting, intelligent climate control, biophilic integration, and sustainable material use, may mitigate these challenges while fostering increasing energy efficiency and occupant well-being. The comfort. This chapter delves into also examines the intersection of technology and interior design, by exploring strategies that leverage on locally available resources, passive design solutions, and digital innovations to create shop-lot offices that are resilient and sustainable workspaces. Special attention is given paid to the cultural and functional demand requirements of shop-lot offices, including their role as multipurpose spaces for commerce and administration. Case studies and insights from tropical regions provide were used to develop a contextual framework for evaluating with which to identify best practices and identifying gaps in current extant design approaches. By highlighting the interplay of correlation between interior design, technology, and environmental responsiveness, this chapter aims to guide interior designers, architects, and policymakers in adopting smarter, more sustainable solutions for shop-lot offices. It concludes by outlining recommendations for future research and practical implementation, emphasising the critical role of interior design in driving sustainability at shop-lot offices in tropical regions.